Shifting the Sun: Solar Spectral Conversion and Extrinsic Sensitization in Natural and Artificial Photosynthesis. Issue 12 (2nd December 2015) - Wondraczek, Lothar; Tyystjärvi, Esa; Méndez‐Ramos, Jorge; Müller, Frank A.; Zhang, Qinyuan
Abstract : Solar energy harvesting is largely limited by the spectral sensitivity of the employed energy conversion system, where usually large parts of the solar spectrum do not contribute to the harvesting scheme, and where, of the contributing fraction, the full potential of each photon is not efficiently used in the generation of electrical or chemical energy. Extrinsic sensitization through photoluminescent spectral conversion has been proposed as a route to at least partially overcome this problem. Here, we discuss this approach in the emerging context of photochemical energy harvesting and storage through natural or artificial photosynthesis. Clearly contrary to application in photovoltaic energy conversion, implementation of solar spectral conversion for extrinsic sensitization of a photosynthetic machinery is very straightforward, and—when compared to intrinsic sensitization—less‐strict limitations with regard to quantum coherence are seen. We now argue the ways in which extrinsic sensitization through photoluminescent spectral converters will—and will not—play its role in the area of ultra‐efficient photosynthesis, and also illustrate how such extrinsic sensitization requires dedicated selection of specific conversion schemes and design strategies on system scale. Abstract : Extrinsic sensitization through solar spectral conversion presents an interesting route for improving the efficiency of natural and artificial photosynthesis for solar‐to‐fuel energy conversion. The role of extrinsic sensitization in photoluminescent spectral converters is here discussed, alongside the necessity of specific conversion schemes and design strategies on system scale.